2013
DOI: 10.3109/07420528.2013.784773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sleep deprivation on rhythms of clock gene expression and melatonin in humans

Abstract: This study investigated the impact of sleep deprivation on the human circadian system. Plasma melatonin and cortisol, and leukocyte expression levels of 12 genes were examined over 48 h (sleep vs no sleep nights) in 12 young males (mean ± SD, 23 ± 5 yrs). During one night of total sleep deprivation BMAL1 expression was suppressed, the heat shock gene HSPA1B expression was induced, and the amplitude of the melatonin rhythm increased while other high-amplitude clock gene rhythms (e.g. PER1-3, REV-ERB) remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 39 publications
5
72
0
1
Order By: Relevance
“…A few hours of sleep deprivation significantly advances the activity onset of hamsters (Antle & Mistlberger, 2000). In humans, BMAL1 is suppressed and melatonin increased in response to sleep deprivation (K. Ackermann et al, 2013;Goh, Tong, Lim, Low, & Lee, 2001). In human subjects, performance and temperature rhythms are altered after one night of total or partial sleep deprivation (Edwards & Waterhouse, 2009;Souissi et al, 2008).…”
Section: Sleep/wake Manipulationmentioning
confidence: 99%
“…A few hours of sleep deprivation significantly advances the activity onset of hamsters (Antle & Mistlberger, 2000). In humans, BMAL1 is suppressed and melatonin increased in response to sleep deprivation (K. Ackermann et al, 2013;Goh, Tong, Lim, Low, & Lee, 2001). In human subjects, performance and temperature rhythms are altered after one night of total or partial sleep deprivation (Edwards & Waterhouse, 2009;Souissi et al, 2008).…”
Section: Sleep/wake Manipulationmentioning
confidence: 99%
“…The underlying mechanisms linking metabolic disease, circadian clock misalignment, and sleep restriction are the subject of current research, elucidation of which will require a global "systems" approach (9). Transcriptomic studies have shown that rhythmic gene expression may be affected by sleep restriction, sleep deprivation, and mistimed sleep (10)(11)(12), but, as yet, no studies have directly investigated the effect that sleep and sleep deprivation may have on the metabolic profile. Metabolic profiling, or "metabolomics," is the profiling of small-molecule metabolites and offers the potential to characterize specific metabolic phenotypes associated with disrupted circadian timing and sleep loss.…”
mentioning
confidence: 99%
“…In a clinical trial, PD patients that were given melatonin showed a minimal improvement in sleep disorders, with no adverse effect resulted from the treatment [54]. Other studies also indicated that melatonin administration resulted in restoration in daily rhythm of various clock genes expression, hence resetting the disturbed circadian pacemaker [55]. Morover, agomelatine, an antidepressant that produces melatonergic effects shows promising results in treating a variety of sleep disorders in PD [56].…”
Section: Melatonin Regulates Circadian Rhythm In Pdmentioning
confidence: 99%